DETERMINASI IMPULSE BUYING MELALUI PROMOSI, DISKON, DAN KUALITAS PELAYANAN PADA PT. MATAHARI DEPARTMENT STORE UPTOWN MALL BSB SEMARANG - Heni Subekti; Navita Cindra Anggraeni (Sekolah Tinggi Ilmu Ekonomi Semarang, 2026)
This study aims to determine the effect of promotions, discounts, and service quality partially on impulse buying. The population in this study were consumers or customers of PT. Matahari Department Store Uptown Mall BSB Semarang. The sampling technique used was a non-probability sampling method with a sample size of 100 respondents. This type of research is quantitative research and the data collection method uses a questionnaire. Data analysis was carried out using multiple linear regression. Based on the results of the study, it can be seen that the promotion and service quality variables have an effect on impulse buying, while the discount variable has no effect on impulse buying. For further researchers, it is recommended to use or add other variables that can influence impulse buying such as price, product quality, socio-cultural influences, and motivation so that they can strengthen the influence on impulse buying